Constructivism to minimal art: from revolution via evolution - Gubbins, Pete (2016)
Modern art owes a debt to Constructivism. In particular, Minimal art owes a debt to Russian Constructivism. In something akin to the suspension of Lenin’s embalmed body, Constructivism has been suspended since its demise. In this thesis I propose that the short-lived phenomenon of Russian Constructivism was revisited and further explored with the Minimal art moment in the West. Minimal artists in the United States were influenced by the works of the Constructivists, but due to the cold war this influence was suppressed. Constructivism in its original form ceased before the ideas and ideological urges of the Russian Constructivists were fulfilled. This form of art, that had a strong connection with a utopian social ideal, by 1932 was replaced by the officially decreed art of the Stalin era; Socialist Realism. The Constructivist moment did not lead into an artistic cul-de-sac because of the death of Lenin in 1924. The Constructivists have had an influence far beyond the years in which they first flourished and I intend to show that Constructivism has been unfairly misrepresented. From my research there is no question that Minimal art in the United States used Constructivist ideas. But the correlation between Minimal art and Constructivism was obscured by cold war politics, by many of the texts which have discussed Constructivism since, as well as by unconvincing curatorial decisions. This situation has led to an unacceptable degree of misrepresentation of the influence that Constructivism has had on Minimal art. Russian and Soviet Constructivism, rather than being seen as a cultural dead-end, should be viewed as a means by which the freedom to follow a non-representational path for abstract art was secured. Constructivism’s influence on Minimal art has been undervalued. This thesis aims to settle the debt.